Melt‐Extruded Sensory Fibers for Electronic Textiles. Issue 3 (26th December 2021) - Tabor, Jordan; Thompson, Brendan; Agcayazi, Talha; Bozkurt, Alper; Ghosh, Tushar K.
Abstract: Textile‐based flexible sensors are key to the development of personal wearable electronic devices and systems for a wide range of applications including physiological monitoring, communication, and entertainment. Textiles, for their many desirable characteristics and use, offer a natural interface between electronics and the human body. A wide range of fabrication techniques have been explored for textile‐based sensors; however, most are not compatible or readily adaptable to textile manufacturing processes. Here, a practical and scalable method of producing textile‐based sensory fibers using a common manufacturing technique, melt extrusion, is proposed. An overview of the fabrication method as well as the mechanical and electrical properties of the fibers is presented. Subsequently, the fibers' ability to sense changes in pressure is studied in detail using assembled fibers. Methods to improve the sensor performance by altering the geometry of the fiber assembly are also presented. As a proof‐of‐concept demonstration, the fibers are woven into a pressure‐sensing fabric mat consisting of 64 sensing elements. The woven substrate can detect the location and level of pressure, thereby illustrating the fibers' potential use as sensors in textile structures. Abstract : Fiber‐based sensors are a part of the future of electronics textiles. Practical design, manufacturing, and integration of these sensors remains elusive because of the incompatibility of the materials and methods with standard textile manufacturing processes. Here, a novel sensory bicomponent fiber and its manufacturing via melt‐extrusion are described. The fibers are subsequently woven into fabrics to form sensory arrays.